Determining Gestational Age in a Low-resource Setting: Validity of Last Menstrual Period (Journal of Health, Population and Nutrition, 2009)
The validity of three methods (last menstrual period [LPM], Ballard and Dubowitz scores) for assessment of gestational age for premature infants in a low-resource setting was assessed, using antenatal ultrasound as the gold standard. It was hypothesized that LMP and other methods would perform similarly in determining postnatal gestational age. Concordance analysis was applied to data on 355 neonates of